PENGARUH SOCIAL MEDIA MARKETING, BRAND AMBASSADOR, DAN BRAND IMAGES TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus pada Brand Erigo Bersama Raffi Ahmad) - Gilang Dian Pratama; Endang Kurniawati (STIE PENA, 2025)
The purpose of this research is to find out whether Social Media Marketing, Brand Ambassadors, and Brand Images influence purchasing decisions. The indepedent variabel in this resarch is Social Media Marketing, Brand Ambassador, and Brand images the variabel Dependent this research is purchasing decision. The data sources in this research are primary and secondary data, obtained by distributing questionnaires to respondents The sample used in this research was 105 respondents from consumers of the Erigo fashion brand in the city of Semarang, especially those aged 17-35 years. The sampling technique used was purposive sampling. The data analysis method uses the SPSS 25 program. The results show that Brand ambassador variable has a positive and significant effect on purchasing decisions, this is proven by the tcount value, namely 2.083 > ttable value 1.660 and a significant value of 0.040 < Î± 0.05 and Brand Images has a positive and significant effect on decisions. Purchase This is proven by the tcount value. 5.191 > ttable value 1.660 and a significant value of 0.000 < Î± 0.05